Measurement Invariance of the Short Home Attachment Scale: A Cross-Cultural Study - Nartova-Bochaver, Sofya; Reznichenko, Sofia; Bardadymov, Vasily; Khachaturova, Milana; Yerofeyeva, Victoria; Khachatryan, Narine; Kryazh, Iryna; Kamble, Shanmukh; Zulkarnain, Zulkarnain (Frontiers in Psychology, 2022)
The home environment is a particularly significant part of life that is supposed to satisfy inhabitants’ needs, form their identity, and contribute to psychological well-being. The construct of home attachment is especially relevant for students as a most mobile social group. This study is devoted to the validation of the Short Home Attachment Scale (SHAS) in a student sample from five countries (Armenia, India, Indonesia, Russia, and Ukraine). A total of 1,349 (17–26 years; Mage = 19.82, SDage = 2.14; 78% females) university students participated in the study and filled in the 14 items Home Attachment Scale (HAS). In order to avoid redundant items with high error covariances damaging the model, a new scale — the Short Home Attachment Scale (SHAS) was developed by eliminating 7 items. The shortened scale has satisfactory structure validity in terms of model fit in all countries except Indonesia; internal reliability values were acceptable in all countries. Measurement invariance across countries was tested with Multi-Group Confirmatory Factor Analysis and Alignment Analysis. Multi-Group confirmatory factor analysis confirmed both configurational and metric invariance. The invariance of item factor loadings, as well as item intercepts, was also confirmed by the Alignment Analysis. The mean scores varied across cultures, with the highest in India and the lowest in Russia. The final version of SHAS is a valid, reliable tool that may be recommended for use in cross-cultural research. However, the SHAS factor structure robustness in the Indonesian population should be investigated thoroughly.